Melioidosis in a domestic cat, with concurrent infestation by nymphs of the cat pentastome, Armillifer moniliformis - Chooi, Kum Fai; Omar, Abdul Rahman; Lee, J. Y. S (Persatuan Doktor Veterinar Malaysia, 1982)
A case of acute fatal melioidosis in the cat is reported. Abscesses were found in the liver, spleen and the left retropharyngeallymph node. A pure culture of Pseudomonas pseudomallei was isolated from the lymph node. The cat also harboured the nympb of ArmiIlifer moniliforrnis, the first record in this speciesfor this parasite